The thymus road to a T cell: migration, selection, and atrophy - Ruiz Pérez, Mario; Vandenabeele, Peter; Tougaard, Peter (Frontiers in Immunology, 2024)
The thymus plays a pivotal role in generating a highly-diverse repertoire of T lymphocytes while preventing autoimmunity. Thymus seeding progenitors (TSPs) are a heterogeneous group of multipotent progenitors that migrate to the thymus via CCR7 and CCR9 receptors. While NOTCH guides thymus progenitors toward T cell fate, the absence or disruption of NOTCH signaling renders the thymus microenvironment permissive to other cell fates. Following T cell commitment, developing T cells undergo multiple selection checkpoints by engaging with the extracellular matrix, and interacting with thymic epithelial cells (TECs) and other immune subsets across the different compartments of the thymus. The different selection checkpoints assess the T cell receptor (TCR) performance, with failure resulting in either repurposing (agonist selection), or cell death. Additionally, environmental cues such as inflammation and endocrine signaling induce acute thymus atrophy, contributing to the demise of most developing T cells during thymic selection. We discuss the occurrence of acute thymus atrophy in response to systemic inflammation. The thymus demonstrates high plasticity, shaping inflammation by abrogating T cell development and undergoing profound structural changes, and facilitating regeneration and restoration of T cell development once inflammation is resolved. Despite the challenges, thymic selection ensures a highly diverse T cell repertoire capable of discerning between self and non-self antigens, ultimately egressing to secondary lymphoid organs where they complete their maturation and exert their functions.